The American Century : Art & Culture 1950-2000 - Anderson, Maxwell L.; Grove, Andrew S.; Phillips, Lisa; W.W. Norton & Company, New York (London New York : Whitney Museum of American Art, 1999)
Acconci, Vito ; Adams, Robert ; Aids, Visual ; Anderson, Laurie ; Andre, Carl ; Anger, Kenneth ; Antin, Eleanor ; Antoni, Janine ; Applebroog, Ida ; Arbus, Diane ; Artschwager, Richard ; Baca, Judy ; Baer, Jo ; Baldessari, John ; Baltz, Lewis ; Bartlett, Jennifer ; Basquiat, Jean-Michel ; Bearden, Romare ; Bechtle, Robert ; Bell, Larry ; Belson, Jordan ; Benglis, Lynda ; Bengston, Billy Al ; Berman, Wallace ; Bickerton, Ashley ; Birnbaum, Dara ; Bleckner, Ross ; Bochner, Mel ; Bontecou, Lee ; Bourgeois, Louise ; Brakhage, Stan ; Breuer, Marcel ; Brody, Sherry ; Brown, Roger ; Brown, Trisha ; Bunshaft, Gordon ; Burton, Scott ; Cage, John ; Campus, Peter ; Celmins, Vija ; Chamberlain, John ; Charlesworth, Sarah ; Chicago, Judy ; Christo & Jeanne-Claude ; CIA, Duro ; Clark, LAARY ; Close, Chuck ; Colescott, Robert ; comic, Alien ; Conner, Bruce ; Conrad, Tony ; DeFeo, Jay ; Diebenkorn, Richard ; Dine, Jim ; Duchamp, Marcel ; Dunham, Carroll ; Durham, Jimmie ; Eames, Charles ; Eggleston, William ; Eisenman, Peter ; Estes, Richard ; Ferber, Herbert ; Fischl, Eric ; Riverhead (New York) ; Frampton, Hollis ; Francis, Sam ; Frank, Robert ; Frankenthaler, Helen ; Freddy, Fab 5 ; Fury, Gran ; Gehry, Frank ; Gober, Robert ; Goldin, Nan ; Golub, Leon ; Gonzalez-Torres, Felix ; Graham, Dan ; Graves, Michael ; Graves, Nancy ; Grooms, Red ; Group, Guerrilla Art Action ; Guston, Philip ; Haacke, Hans ; Halley, Peter ; Hamilton, Ann ; Hammons, David ; Hanson, Duane ; Haring, Keith ; Hartigan, Grace ; Heizer, Michael ; Held, Al ; Herms, George ; Hesse, Eva ; Hill, Gary ; Hodges, Jim ; Hofmann, Hans ; Holt, Nancy ; Holzer, Jenny ; Hopper, Edward ; Huebler, Douglas ; Hujar, Peter ; Hunt, Bryan ; Indiana, Robert ; Irwin, Robert ; Jacobs, Ken ; Jenney, Neil ; Johns, Jasper ; etc.
The American Century : Art & Culture 1950-2000, Whitney Museum of American Art, New York, Part I, 1900-1950, April 23 to August 22, 1999, and Part II, 1950-2000, September 26, 1999 to February 13, 2000
Engels
boek
Keywords: Amerika